Critical Skills Development Discussion Amsilati Pondok Pesantren API Asri Tegalrejo - Siti Nailatul Muflihah; Siswanto; Dakusta Puspitasari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
In modern education, the cultivation of critical skills among students is paramount to address the complexities of the 21st century. This study investigates the efficacy of amsilati class discussions in fostering critical skills development, addressing a gap in understanding the true impact of this innovative learning approach. Utilizing Participatory Action Research (PAR) methodology, the research engages stakeholders in Islamic boarding schools to collaboratively assess the influence of amsilati discussions on students' critical skills. Data collection involves class observations, teacher interviews, and pre- and post-application tests. Findings reveal significant enhancements in students' ability to analyze information, construct arguments, and engage actively in discussions. Teachers play a pivotal role as facilitators and mentors, guiding students in honing critical thinking skills. Evaluation of student progress highlights increased participation, improved dialogue quality, and a positive learning atmosphere. The study underscores the importance of continuous evaluation and adaptation of learning strategies to nurture critical thinking among students, equipping them to navigate contemporary challenges effectively.